2017
DOI: 10.1111/modl.12380
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Language Mindsets and Modeling Their Relations With Goal Orientations and Emotional and Behavioral Responses in Failure Situations

Abstract: Some people ascribe successful language learning to an innate aptitude that cannot be further developed, at least after a certain young age (i.e., an entity mindset), while other people believe that language learning ability can be improved (i.e., an incremental mindset). The purpose of this research is to (a) introduce the Language Mindsets Inventory (LMI), and (b) test the mindsets-goals-responses model, which maintains that learners' mindsets predict the goals that they set for language learning, and that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
155
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 169 publications
(171 citation statements)
references
References 57 publications
(138 reference statements)
12
155
2
2
Order By: Relevance
“…The second analysis was run with two factors predetermined to be extracted. The results showed that the two factors (Appendix ), representing a Growth L2 Mindset and a Fixed L2 Mindset , explained 75.7% of the variance, confirming the two‐factor solution emerged in the studies by Lou and Noels () and Waller and Papi (). In addition, Kaiser–Meyer–Olkin measure of sampling adequacy (.91) was excellent (i.e., >.05), and Bartlett's test of sphericity was statistically significant (χ2(29) = 1975.29, p < .001), indicating a good fit for the dataset.…”
Section: Methodssupporting
confidence: 74%
See 3 more Smart Citations
“…The second analysis was run with two factors predetermined to be extracted. The results showed that the two factors (Appendix ), representing a Growth L2 Mindset and a Fixed L2 Mindset , explained 75.7% of the variance, confirming the two‐factor solution emerged in the studies by Lou and Noels () and Waller and Papi (). In addition, Kaiser–Meyer–Olkin measure of sampling adequacy (.91) was excellent (i.e., >.05), and Bartlett's test of sphericity was statistically significant (χ2(29) = 1975.29, p < .001), indicating a good fit for the dataset.…”
Section: Methodssupporting
confidence: 74%
“…In addition, the relationship between Growth L2 Mindset and Feedback Monitoring was partially mediated by Development-Approach. These results confirm that learners with a growth mindset and development-approach goals tend to perceive setbacks such as being corrected as opportunities for growth, attribute gaps in their competence to their efforts and strategies rather than their abilities, and take action to improve their competence through the use of extra effort and better strategies (e.g., Dweck, 1999;Hong et al, 1999;Lou & Noels, 2017;Mangels et al, 2006). Therefore, these learners are not typically concerned with the ego and self-presentation costs of feedback monitoring due to their tendency to focus on developing rather than validating their L2 abilities.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…However, there are some papers in which DM is used for each isolated application, for instance learner motivation (13% of papers), learning styles (8%), provide feedback for instructors (9%), detecting language anxiety (6%), predicting performance (14%), L2 orientations (8%), language reading comprehension (5%), and detecting grammar issues and assessment (7%). In this analysis, the DM applications most frequently used in the context of FLL are: Predicting performance (Linck et al, 2013;Seker, 2016;Swanson et al, 2016;Wang & Cheng, 2016;Whitehill & Movellan, 2018), learner motivation (Apple, Falout, & Hill, 2013;Li & Zhou, 2017;Saeed et al, 2014;Tajeddin & Moghadam, 2012), provide feedback for instructors (Coskun & Mutlu, 2017;Jiang & Lee, 2017;Kaoropthai, Natakuatoong, & Cooharojananone, 2016;Kieffer & Lesaux, 2012;Rodriguez & Shepard, 2013;Zhao et al, 2015), learning styles (Aslan et al, 2014;Farrington et al, 2015;Hamedi, Pishghadam, & Ghazanfari, 2016;Hsiao, Lan, Kao, & Li, 2017), detecting language anxiety (Baghaei & Ravand, 2015;Cakir & Solak, 2014;Guntzviller et al, 2016;Martin & Valdivia, 2017), and L2 orientations (Allen et al, 2014;Lou & Noels, 2017;Maqsood et al, 2016;Winke, 2013). Figures 8 and 9 show the correlation between the educational level in where the articles mentioned to have developed their proposal and the EDM methods and applications that has been used, respectively.…”
Section: Edm Methods Referencesmentioning
confidence: 99%